2022
DOI: 10.1038/s44160-022-00075-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Möbius carbon nanobelt

Abstract: Technologies for the creation of topological carbon nanostructures have greatly advanced synthetic organic chemistry and materials science. Although simple molecular nanocarbons with a belt topology have been constructed, analogous carbon nanobelts with a twist—more specifically, Möbius carbon nanobelts (MCNBs)—have not yet been synthesized owing to their high intrinsic strain. Here we report the synthesis, isolation and characterization of a MCNB. Calculations of strain energies suggest that large MCNBs are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
83
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(88 citation statements)
references
References 40 publications
4
83
0
1
Order By: Relevance
“…In 2022, Segawa et al . [14] successfully synthesized Mobius carbon nanobelts with a green-blueish fluorescence. Graphene-like hexagonal boron-nitride has become a new potential material for gas sensing among researchers.…”
Section: Introductionmentioning
confidence: 99%
“…In 2022, Segawa et al . [14] successfully synthesized Mobius carbon nanobelts with a green-blueish fluorescence. Graphene-like hexagonal boron-nitride has become a new potential material for gas sensing among researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, Itami and Segawa et al demonstrated the first successful synthesis of a fully fused and fully conjugated Möbius carbon nanobelt. 22 Considering the key strain problem, DFT calculations were conducted in advance of the experimental operations to evaluate the theoretical feasibility of target Möbius carbon nanobelts. According to the calculation results, (25, 25)MCNB ( 21 ) and (15, 15)MCNB ( 23 ) with 5 and 3 repeat units, respectively, were preferentially selected as the target molecules in view of the fact that an even number of repeat units would lead to only the CNB product.…”
Section: Conjugated Molecular Möbius Stripsmentioning
confidence: 99%
“…In artificial systems, various bottom-up synthetic strategies have been developed for building up a myriad of synthetic macromolecules. To emulate the complexity and functionality of natural substances, increasing attention has been concentrated on precise synthesis of macrocycles, helical polymers or foldamers, nanoribbons or ladder polymers, , and so forth., with a rigid backbone for facilitating the design and control of desired configurations. For example, many foldamers with aromatic skeletons are designed with monomers having a “V” convergent shape (Figure S1).…”
Section: Introductionmentioning
confidence: 99%